Pelatihan Pembuatan Laporan Keuangan Pada Usaha Pondok Bakso Bakar Dan Minuman - Helmiati Helmiati (Asosiasi Dosen Akuntansi Indonesia, 2021)
This activity started from the need for financial reports needed by traders, especially small traders. Lack of understanding, lack of training, and perceptions of complicated financial reporting make this activity carried out. Some of the problems faced by partners can be handled properly when the activity is held. The method used in this activity is the lecture method and the practical method of making financial reports. From the results of lectures, discussions, and Q&A, our team can conclude that business actors already understand how to increase family income and gain market share. The team can ensure that there is free time and the ability to progress and can help the family's economy.